SIKAP DAN PERILAKU KONSUMEN RUMAH TANGGA TERHADAP PRODUK RAMAH LINGKUNGAN - Sutrisno Sutrisno (Jurnal Pendidikan Ilmu Sosial, 2021)
In increasing awareness of environmental safety and health, various parties, both individuals and groups, have done various things to the community so that it leads to household consumers. The purpose of this study was to find out whether the attitudes and behavior of household consumers on environmentally friendly products in Kapas District, Bojonegoro Regency were consistent. This study was analyzed using descriptive and inferential statistics. Descriptive statistical analysis used the average score category, while the Spearman Rank correlation coefficient analysis was used. The results showed that the attitudes and behavior of household consumers tend to be contradictory. The attitudes of household consumers tend to be in the high and very high categories. Behavior is in the low category. The results of the Spearman rank correlation analysis of household consumer attitudes and behavior are not always consistent, even the parameters are contradictory.